PENGARUH MEDIA SOSIAL TIKTOK TERHADAP KEBUTUHAN INFORMASI SEKS EDUKASI PADA GENERASI Z - Ramadhan, Ahmad Fahri; Ramdhani, Muhammad; Utamidewi, Wahyu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Sex education is still a topic that is considered taboo in Indonesia, through Tiktok which is a popular application in the world in 2020, it is used as a medium to meet this information need by the @tabu.id account. The purpose of this study was to determine the effect of intensity, media content and attractiveness of using social media on the TikTok @tabu.id account on the fulfillment of sex education information needs. This study uses a quantitative approach with an explanatory survey. The theory used is the Uses Effect Theory. The data collection technique used is a questionnaire or questionnaire and literature study. While the data analysis technique will be collected using a Likert scale. The results of this study are the intensity, message content and attractiveness affect the need for information about sex education. While the magnitude of the influence of sex education information is 6.75%, the magnitude of the influence of infographic messages on sex education information is 33.26% and the magnitude of the influence of sex education information is 15.02%.